Biomedical informatics advancing the national health agenda: the AMIA 2015 year-in-review in clinical and consumer informatics. (7th August 2016) - Roberts, Kirk; Boland, Mary Regina; Pruinelli, Lisiane; Dcruz, Jina; Berry, Andrew; Georgsson, Mattias; Hazen, Rebecca; Sarmiento, Raymond F; Backonja, Uba; Yu, Kun-Hsing; Jiang, Yun; Brennan, Patricia Flatley
Abstract : The field of biomedical informatics experienced a productive 2015 in terms of research. In order to highlight the accomplishments of that research, elicit trends, and identify shortcomings at a macro level, a 19-person team conducted an extensive review of the literature in clinical and consumer informatics. The result of this process included a year-in-review presentation at the American Medical Informatics Association Annual Symposium and a written report (see supplemental data). Key findings are detailed in the report and summarized here. This article organizes the clinical and consumer health informatics research from 2015 under 3 themes: the electronic health record (EHR), the learning health system (LHS), and consumer engagement. Key findings include the following: (1) There are significant advances in establishing policies for EHR feature implementation, but increased interoperability is necessary for these to gain traction. (2) Decision support systems improve practice behaviors, but evidence of their impact on clinical outcomes is still lacking. (3) Progress in natural language processing (NLP) suggests that we are approaching but have not yet achieved truly interactive NLP systems. (4) Prediction models are becoming more robust but remain hampered by the lack of interoperable clinical data records. (5) Consumers can and will use mobile applications for improved engagement, yet EHR integration remains elusive.